The enforcement of Halal certification in Pahang Darul Makmur: addressing the practical challenges - Ahmad Bustami, Tajul Aris (2018)
Presently, the enforcements on halal certification in Pahang Darul Makmur are fully conducted by the officers from the Ministry of Domestic Trade, Co-operatives and Consumerism (Kementerian Perdagangan Dalam Negeri, Koperasi dan Kepenggunaan - KPDNKK), with the assistance of the Syariah Religious Officers from Jabatan Agama Islam Pahang. The suspects were then brought to the civil courts for trial. No case has even been brought to the syariah courts even though the offence relating to abuse of halal sign is provided in Syariah Criminal Offences Enactment 2013 (Enactment No. 11 of 2013). Section 51 of the enactment provides that any related offences are punishable with fine of not exceeding RM5000, imprisonment of not exceeding 3 years, whipping of not exceeding 6 strokes or any combination thereof. The fact that the cases were tried by the civil courts has raised an issue on the competency and capabilities of the religious authorities in dealing with the halal infringement cases in Pahang. This paper aims to look into the background of the scenario, issue of jurisdictions and numerous constraints faced by the religious authorities that hampered the effectiveness of the enforcement. Based on the data gathered through interviews, case reports and courts decisions, recommendations for the improvement of the enforcement will be proposed.